1992
DOI: 10.1128/iai.60.7.2657-2666.1992
|View full text |Cite
|
Sign up to set email alerts
|

Purification of recombinant Helicobacter pylori urease apoenzyme encoded by ureA and ureB

Abstract: Helicobacter pyloni, a gram-negative, microaerophilic, spiral-shaped bacterium, is an etiologic agent of human gastritis and peptic ulceration and is highly restricted to the gastric mucosa of humans. Urease, synthesized at up to 6% of the soluble cell protein, hydrolyzes urea, thereby releasing ammonia, which may neutralize acid, allowing survival of the bacterium and initial colonization of the gastric mucosa. The urease protein is encoded by two subunit genes, ureA and ureB; however, accessory genes are nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 40 publications
1
47
0
2
Order By: Relevance
“…Previous studies identified the presence of seven accessory urease genes for H. pyiori; three of these genes were shown to be essential for urease expression in E. coii (Cussac etai., 1992;Labigne etai., 1991). The requirement for accessory genes in the synthesis of an active urease enzyme has been well established for numerous microbial ureases, including H. pyiori (Hu et al, 1992;Mobley and Hausinger, 1989). Recent data confirmed that accessory urease genes are involved in the incorporation of nickel ions into the metallocentre of Kiebsieiia aerogenesurease (Lee etai., 1992).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies identified the presence of seven accessory urease genes for H. pyiori; three of these genes were shown to be essential for urease expression in E. coii (Cussac etai., 1992;Labigne etai., 1991). The requirement for accessory genes in the synthesis of an active urease enzyme has been well established for numerous microbial ureases, including H. pyiori (Hu et al, 1992;Mobley and Hausinger, 1989). Recent data confirmed that accessory urease genes are involved in the incorporation of nickel ions into the metallocentre of Kiebsieiia aerogenesurease (Lee etai., 1992).…”
Section: Discussionmentioning
confidence: 88%
“…Among the ureI gene sequences available from 21 strains of H. pylori , there is very high identity with only a few largely conservative substitutions (V42I, V45I, H54N, V66A, S74N and V116I). For the mutagenesis experiments, ureI was amplified by polymerase chain reaction (PCR) from the plasmid pHp808 (Hu et al ., 1992), which encodes the identical protein sequence to the reference strain H. pylori J99. Mutagenesis was carried out by a two‐step PCR method (Ho et al ., 1989).…”
Section: Methodsmentioning
confidence: 99%
“…Isogenic urease-negative mutants of H. pylori have been constructed and used to demonstrate that urease was not required for the survival of H. pylori in vitro but was essential for colonization of the gastric mucosa in piglets (12) and mice (32). Like the other bacterial ureases, the H. pylori urease is a metalloenzyme that requires nickel ions for activity (6); however, unlike these other ureases, it consists of a heteropolymer of two [(AB) 3 ], not three [(ABC) 3 ], subunits (4,19,21). Although mostly found in the cytoplasmic compartment, it is also present in association with the outer membrane and as released subcellular material (14,17).…”
mentioning
confidence: 99%